SUPPORT VECTOR MACHINE AND K- NEAREST NEIGHBOR BASED ANALYSIS FOR THE PREDICTION OF HYPOTHYROID - K.SARAVANA KUMAR; DR. R. MANICKA CHEZIAN (International Journal of Pharma and Bio Sciences, 2014)
The thyroid gland produces two important hormones T3 (triiodothyronine) and T4 (thyroxine). These hormones contain in the blood and control many undertakings in human bodies. Calories burning, heartbeats are supervised by T3 and T4. This is called human body metabolism. The thyroid, which is in good condition, produces as required amounts of hormones for the function of good mechanism of metabolism. The thyroid illness mostly affects women than men. Hypothyroidism and Hyperthyroidism are the two levels of thyroid malfunction. In data mining, Support Vector Machine (SVM) and K-Nearest Neighbor (KNN) are the two important modes applied to the prediction of hypothyroid. This paper discusses that predictions of Hypothyroid using K- Nearest Neighbor better than the Support Vector Machine.